Comportamento de pilares mistos preenchidos com concreto refratário de alto desempenho à temperatura ambiente e em situação de incêndio - Rodrigo Eduardo Niquini da Costa (2005)
In this work the axial compressive strength for composite columns made by circular or rectangular tube filled with high performance refractory concrete (CRAD), under fire condition or under usual condition, is determined and its compressive strength is compared with that composite columns filled with conventional concrete. Also a new method by table to design composite columns filled with CRAD is developed. This new method follows the logical of the method of design by table from the review text of the standard NBR 14323 (2003) that attends the design of composite structures under fire condition. The temperature distribution in the columns is obtained by a software THERSYS, based on the Finite Element Method. The axial strength for composite columns is obtained by a software PCRAD, developed in this work, that attend the method of the review text of the standard NBR 8800 (2003). The results are columns more resistant or columns with smaller cross section